Program Kampung Tepa Salira Sebagai Upaya Penguatan Toleransi dan Moderasi Beragama Masyarakat Multikultural Kelurahan Tlogomas, Kota Malang - Nada, Auqi Lu'lu In; Arifin, As'ad Syamsul; Anggraini, Tasha Monica; Sultoni, Achmad (Politeknik Piksi Ganesha Indonesia, 2024)
The differences in ethnicity, religion, race, and intergroup in Tlogomas Village make it a multicultural area. In addition, the large number of seasonal migrants (students from outside the region) adds to the multicultural nuances in this village so that conflicts between groups are difficult to avoid. This community service aims to realize Tlogomas Village into a Tepa Salira Village that upholds religious moderation and tolerance. To achieve this goal, 5 integrated programs were implemented, namely the intensive and weekend class corner, Pancasila corner, religious literacy corner, Bhinneka Tunggal Ika corner, and cultural creativity corner. The five programs were implemented by involving various stakeholders in a synergistic manner, including village government figures, security figures, university academics, the Religious Harmony Forum (FKUB) of Malang City, religious and community leaders, youth organizations, and local campus organizations. This activity was able to improve the tolerant attitude among them. One of the indications is seen from the change in the attitude of children who have become more polite, as well as the establishment of cooperation between youth organizations and regional organizations.